2014
DOI: 10.4269/ajtmh.13-0484
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and Risk Factors for Hospital-Acquired Diarrhea in Three Tertiary Care Public Hospitals in Bangladesh

Abstract: During April 2007–April 2010, surveillance physicians in adult and pediatric medicine wards of three tertiary public hospitals in Bangladesh identified patients who developed hospital-acquired diarrhea. We calculated incidence of hospital-acquired diarrhea. To identify risk factors, we compared these patients to randomly selected patients from the same wards who were admitted > 72 hours without having diarrhea. The incidence of hospital-acquired diarrhea was 4.8 cases per 1,000 patient-days. Children < 1 year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…5,22,32 Hospitalacquired infections are a major problem in health facilities in Bangladesh. 3 This problem is intensified by inadequate hand hygiene practices in this settings.…”
Section: Discussionmentioning
confidence: 99%
“…5,22,32 Hospitalacquired infections are a major problem in health facilities in Bangladesh. 3 This problem is intensified by inadequate hand hygiene practices in this settings.…”
Section: Discussionmentioning
confidence: 99%
“…The leading non-surgical HAIs include respiratory and gastrointestinal illnesses. The incidence of hospital-acquired diarrhea at three tertiary care public hospitals was 4.8 cases per 1000 patient days during the 2007-2010 period [25]. Transmission was through fecal-oral route.…”
Section: Review Of Existing Literature On Hospital Acquired Infectionmentioning
confidence: 99%
“…For example, a large outbreak of Nipah virus was reported among healthcare workers and patients at hospitals in Siliguri, India in 2001 and evidence of Nipah virus transmission in Bangladesh has recently been reported [3]. In addition, patients in Bangladeshi hospitals face substantial risks from endemic infections; studies have shown that hospital-acquired respiratory infections occur at an incidence rate of 6.1 cases per 1000 patientdays [5], and diarrhea with an incidence rate of 3.9 cases among pediatric patients and 2.7 cases among adults per 1000 patientdays [6].…”
Section: Introductionmentioning
confidence: 99%